Development of the Impact of Nighttime Urination (INTU) questionnaire to assess the impact of nocturia on health and functioning. Issue 5 (22nd March 2018) - Abrams, Steven; Martin, Susan; Gillard, Kristin K.; Cheng, Linda; Fein, Seymour
Abstract : Aims: This study describes development of the Impact of Nighttime Urination (INTU) questionnaire to assess nocturia impacts on health and functioning. Methods: Development of the questionnaire followed an iterative patient‐directed process as recommended by current guidance for patient‐reported outcome (PRO) measures. An initial 15‐item questionnaire was devised based on reviewing the published literature, and then modified through four rounds of semi‐structured interviews of 28 individuals with nocturia. In each round, open‐ended concept elicitation, followed by cognitive debriefing, was used to assess the questionnaire. Items were modified based on participants' responses and incorporated into the next round of interviews. Results: In all rounds, participants reported that their experiences were easy to recall and report on a daily basis and that the burden of completing the questionnaire was low. The final questionnaire has a same‐day recall period. It includes six daytime impact items—having limited concentration, a sense of feeling tired, difficulty getting things done, irritability, not feeling rested, and drowsiness—and four items that measure the nighttime impact of nocturia—patient concern, waking up too early, difficulty getting enough sleep, and feeling bothered by having to get up at night to void. Responses follow a 5‐ or 4‐point scale. The final INTU captures the key concepts associated with nocturia as confirmed by cognitive debriefing. Conclusions: Development of the 10‐item INTU, a nocturia‐specific PRO measure, was based on direct input and feedback from patients and has demonstrated that it captures the patient‐reported impacts of nocturia.